The Influence of Digital Literacy and Civic Literacy on Civic Responsibility among Prospective Teachers - Maulani, Ananda Allyssa Listiyana; Patmisari, P (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyse the influence of digital literacy and civic literacy on civic responsibility among prospective teachers.Methodology: The study employs a quantitative descriptive methodology with a correlational design, using purposive random sampling. The research population consists of 2.791 people, and the research sample consists of 247 students from the Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta.Results: The results show that all three research hypotheses were proven and accepted. The t-value for digital literacy was 3.247 > t-table 1.651, and the t-value for civic literacy was 9.992 > t-table 1.651, indicating that H1 was accepted. Digital literacy and civic responsibility are positively correlated, and H2 is approved, indicating a favorable impact between civic literacy and civic responsibility. The F-test indicates that both literacies positively affect civic responsibility. These findings indicate that the higher the levels of digital literacy and civic literacy among prospective teachers, the higher their awareness and sense of responsibility as citizens, both in real life and the digital space. Digital literacy and civic literacy help students understand their actions and consequences in the digital and real worlds, thereby fostering a stronger sense of civic responsibility.Applications/Originality/Value: This research can be applied in the development of curricula and learning strategies for Pancasila and Civic Education. The novelty of this research lies in the simultaneous empirical testing of digital and civic literacy to analyse the formation of civic responsibility in the digital age, this area has not been widely studied among prospective teachers.